Inhibition of anti-tumor immunity by melanoma cell-derived Activin-A depends on STING - Pinjusic, Katarina; Ambrosini, Giovanna; Lourenco, Joao; Fournier, Nadine; Iseli, Christian; Guex, Nicolas; Egorova, Olga; Nassiri, Sina; Constam, Daniel B. (Frontiers in Immunology, 2024)
The transforming growth factor-β (TGF-ꞵ) family member activin A (hereafter Activin-A) is overexpressed in many cancer types, often correlating with cancer-associated cachexia and poor prognosis. Activin-A secretion by melanoma cells indirectly impedes CD8 + T cellmediated anti-tumor immunity and promotes resistance to immunotherapies, even though Activin-A can be proinflammatory in other contexts. To identify underlying mechanisms, we here analyzed the effect of Activin-A on syngeneic grafts of Braf mutant YUMM3.3 mouse melanoma cells and on their microenvironment using single-cell RNA sequencing. We found that the Activin-A-induced immune evasion was accompanied by a proinflammatory interferon signature across multiple cell types, and that the associated increase in tumor growth depended at least in part on pernicious STING activity within the melanoma cells. Besides corroborating a role for proinflammatory signals in facilitating immune evasion, our results suggest that STING holds considerable potential as a therapeutic target to mitigate tumor-promoting Activin-A signaling at least in melanoma.